Traces of goitre in some archaeological finds - Baggieri, Gaspare; Galieti, Luigi; Di Matteo, Giorgio (Medicina Historica, 2021)
The authors provide an original interpretation regarding two finds from archaeological excavations in health-sanctuary areas of Lazio (Latium). They believe that the presence of goitre may be detected by reading two female terracotta ex voto suscepto sculptures dating back, respectively, to the fifth-third and second centuries BCE. The two sites are located in the Lazio region but they are distant from each other though historically known for the presence of endemic goitre.